Advancements in Cloud-Native Applications: Innovative Tools and Research Frontiers - Krishna Rao Vemula, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores the cutting-edge developments in cloud-native applications, focusing on innovative tools and research frontiers that are shaping the future of digital infrastructure. It examines the evolving capabilities of orchestration platforms, the integration of IoT and edge computing, advancements in serverless architectures, and the growing importance of AI-driven optimization and sustainable computing practices. The article delves into case studies across e-commerce, healthcare, and financial services sectors, illustrating how cloud-native technologies are being leveraged to solve complex business challenges and drive innovation. Key tools such as Kubernetes, observability platforms, and microservices development frameworks are discussed, highlighting their role in enabling efficient, scalable, and resilient cloud-native applications. The article also considers the broader impact of these technologies on digital service delivery, emphasizing the benefits for businesses in terms of agility, user experience, and competitive advantage. Finally, it underscores the critical importance of collaboration among academia, industry, and open-source communities in driving future advancements in the cloud-native ecosystem, painting a picture of a dynamic and rapidly evolving technological landscape with far-reaching implications for the future of computing.
Keywords: Cloud-native applications; Kubernetes orchestration; Serverless computing; Microservices architecture; Edge computing integration